PENERAPAN NILAI KODE ETIK KEDOKTERAN INDONESIA PADA ERA JAMINAN KESEHATAN NASIONAL DI KABUPATEN INDRAGIRI HULU - Sunki Yulia Dwi P; Dedi Afandi; Desby Juananda (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTThe Indonesian Medical Codes of Ethics or Kode Etik Kedokteran Indonesia (KODEKI) is a set of ethical profession which used by the doctor in Indonesia as their basic guidelines to behave. In 1st January 2014, Jaminan Kesehatan Nasional or National Health Coverage (NHC) officially applied in Indonesia including Indragiri Hulu Regency. Therefore, to handle the increasing amount of patients in NHC’s era, a general practitioner as a gatekeeper had to still apply the KODEKI. The aim of this research is to know how is the implementation of KODEKI in NHC’s era in Indragiri Hulu Regency. This research uses the design of exploration method with qualitative approach on four general practitioners. The informants of this research were selected by using snowball sampling method which suitable with inclusion criteria. This research was done by interview method with question’s lists and recorded with an audio recorder. The result showed that all of the informants possess altruism, responsibility, professional idealism, accountability, scientific integrity, and social integrity. It showed that general practitioners in NHC’s era in Indragiri Hulu Regency are still applying KODEKI.Keywords : KODEKI values, NHC, Indragiri Hulu